(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The importance of innovation was long underestimated in service activities. In contrast to the radical innovations vital to growth in manufacturing sectors, innovations in services and tourism were secondary and capital-scarce, and for this reason they were excluded from the scope of government interest and action. It is interesting to note that the discourse changed with the emergence of new information and communication technologies.